Dick Bierman letter to Nicholas S. Halmi regarding spring bird sightings, May 28, 1979 - Bierman, Dicket al (1979)
Letter from Dick Bierman to Nicholas S. Halmi regarding spring bird sightings in northwest Iowa, May 28, 1979. A rare sighting of a Purple Sandpiper was noted. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed